The role of surface stoichiometry in NO2gas sensing using single and multiple nanobelts of tin oxide - Masteghin, Mateus G. [UNESP] (2021)
Typically used semiconducting metal oxides (SMOs) consist of several varying factors that affect gas sensor response, including film thickness, grain size, and notably the grain-grain junctions within the active device volume, which complicates the analysis and optimisation of sensor response. In comparison, devices containing a single nanostructured element do not present grain-grain junctions, and therefore present an excellent platform to comprehend the correlation between nanostructure surface stoichiometry and sensor response to the depletion layer (Debye length,LD) variation after the analyte gas adsorption/chemisorption. In this work, nanofabricated devices containing SnO2and Sn3O4individual nanobelts of different thicknesses were used to estimate theirLDafter NO2exposure. In the presence of 40 ppm of NO2at 150 °C,LDof 12 nm and 8 nm were obtained for SnO2and Sn3O4, respectively. These values were associated to the sensor signals measured using multiple nanobelts onto interdigitated electrodes, outlining that the higher sensor signal of the Sn4+surface (up to 708 for 100 ppm NO2at 150°) in comparison with the Sn2+(up to 185) can be explained based on a less depleted initial state and a lower surface electron affinity caused by the Lewis acid/base interactions with oxygen species from the baseline gas. To support the proposed mechanisms, we investigated the gas sensor response of SnO2nanobelts with a higher quantity of oxygen vacancies and correlated the results to the SnO system.